Effect of bearing thermally induced preload on the efficiency of automotive manual transmission under RDE. (November 2019) - Laderou, A; Mohammadpour, M; Theodossiades, S; Wilson, A; Daubney, R
In order to calculate the efficiency of an automotive manual transmission, taking into consideration the effect of its most power consuming components – gears and bearings – as well as the interactions between them is of high importance. In this paper, a dynamic model has been developed which can predict the frictional losses of a complete gearbox as a system and, thus, its efficiency. The effect of temperature on bearing preload is also considered and taken into account from a system perspective identifying its effect on the bearings frictional losses (as well as the overall efficiency). The operating conditions used are snapshots of the Real Driving Emissions driving cycle, which is a standard metric for automotive manufacturers. Results show that doubling the temperature can lead to 120% increase of the bearing losses and up to 140% increase of the total transmission losses. The effect of the variation of operating conditions (velocity and torque) is also taken into account. The novelty of this paper lays in the development of a dynamic model which takes into account the performance of a complete gearbox under transient operating conditions, as well as the interaction among its main components and the ability to make changes on the influencing factors of transmission efficiency so that their effect on the complete gearbox efficiency can be tracked. This has not been yet reported in the relevant literature which mainly focuses on the influencing factors of transmission power loss and efficiency experimental measurements under various operating conditions for gear pairs instead of complete gearboxes.